Sasi Laut as a Culture of Natural Resources Conservation to Overcome the Tragedy of the Commons in Maluku Province - Muin, Abdul; Rakuasa, Heinrich (International Journal of Multidisciplinary Approach Research and Science, 2023)
This research focuses on the cultural practice of conservation known as "Sasi Laut" in the Maluku Islands, Indonesia, and how this practice plays a role in overcoming the "Tragedy of the Commons" in natural resource management. "Tragedy of the Commons" refers to a situation where the shared use of natural resources by a number of parties leads to over-exploitation to the detriment of all. This research is based on a qualitative approach with data collection through in-depth interviews, participatory observation, and documentation studies related to local customs and traditions. The results show that Sasi Laut is a practice that emerged from the local wisdom of the Maluku Islands community to maintain the sustainability and abundance of natural resources. Sasi Laut is implemented by setting restrictions or prohibitions on the use of certain natural resources in certain water areas for a certain period of time. Through this system, local communities collaborate in monitoring and enforcing mutually agreed rules. This practice is not only rooted in local tradition and culture, but also forms strong social ties among community members. This research also analyzes the effectiveness of Sasi Laut in preventing natural resource degradation and promoting conservation. The results show that Sasi Laut has been successful in maintaining the sustainability of the marine ecosystem and preventing overexploitation. In addition, this practice also maintains the cultural heritage and traditions of the Maluku people who are attached to nature and their environment. In conclusion, this research provides a deeper understanding of how cultural practices such as Sasi Laut can be a valuable solution in addressing the "Tragedy of the Commons" and opens up opportunities to apply similar approaches in other regions facing similar problems in natural resource management. Collaborative efforts by communities and government to preserve and promote Sasi Laut practices are essential to achieve long-term conservation and sustainable development goals.